Characteristic of â€œBetutu Chicken â€in Many Different Packaging Stored at 50C - Suciani Suciani; Ida Ayu Okarini; Made Dewantari; Anak Agung Oka (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2009)
â€œBetutu chickenâ€ (whole chicken) is traditional Balinese food. Originally was cooked for ritual offerings, but recently this food was one of the menu in hotels or restaurants in Bali. Research was carried out using completely randomized design (CRD) with 3 different packaging treatment, such as treatment one was using alumunium foil, treatment too using banana leaf and alumunium foil and treatment three using â€œUpihâ€ and alumunium foil. Whole chicken was squeezed with salt and tamarin, and then wash with water. Put into the cavity of the chicken all spices and Â½ glass of cooking oil, close the cavity and wrap up according to the treatment then cooked in the live coal for (8 â€“ 11) hours. After cooked and then stored at 50 C. the organoleptic test showed that this product keep for 7 days in 50 C still can safe and excepted by the consumen with organoleptic score between 6.0 â€“ 7.0 in overall. Objective test showed that (p<0.05) for 3 treatment to pH (6.2 â€“ 6.4), water content (44 â€“ 48)%, water holding capacity 68 â€“ 70% and total aerobic count 4.503 â€“ 5.041 cfu/g. Â  Keywords: Betutu chicken, Alumunium foil, â€œUpihâ€, Banana Leaf, Storage 50 C